2022
DOI: 10.15603/2176-1078/er.v36n3p95-119
|View full text |Cite
|
Sign up to set email alerts
|

A Psicanálise e o triunfo da Religião

Abstract: Há uma intrínseca relação entre a psicanalise e a religião que precisa ser compreendida para que melhor consigamos entender o fenômeno religioso nos dias atuais. Analisaremos a Religião a partir da psicanálise, em especial, refletindo acerca da concepção de Pai primeiro em Freud e Pai simbólico em Lacan, bem como a formação da função paterna e seu papel de alteridade e de fundamentação e legitimação na cultura Ocidental. Discutiremos as concepções de ambos os autores citados sobre suas respectivas projeções do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…This present study presents the initial results of the research project "Rites and myths in Augustus literature", and aims to analyze the Carmen saeculare by Horace, searching to emphasize your structuring, political and moral values presented in the text, and the presence of ritualistic elements related to the Secular Games. In methodological terms, after the translation and researches about the poem structure, based on Souza (2013), we opted to initiate a study about the moral and political ideals of the Roman man that were observed in the Carmen, taking as an starting point the arguments from Maria Helena da Rocha Pereira (1990), and investigate the presence of gods and heroes from Aeneas, following initially the study of Junito Brandão (1993) regarding the version of the myths, in addition to the choice of Cassirer (2009) for the initial reflexions about the subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This present study presents the initial results of the research project "Rites and myths in Augustus literature", and aims to analyze the Carmen saeculare by Horace, searching to emphasize your structuring, political and moral values presented in the text, and the presence of ritualistic elements related to the Secular Games. In methodological terms, after the translation and researches about the poem structure, based on Souza (2013), we opted to initiate a study about the moral and political ideals of the Roman man that were observed in the Carmen, taking as an starting point the arguments from Maria Helena da Rocha Pereira (1990), and investigate the presence of gods and heroes from Aeneas, following initially the study of Junito Brandão (1993) regarding the version of the myths, in addition to the choice of Cassirer (2009) for the initial reflexions about the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Ideais, deuses e ritos: uma análise do Carmen saeculare horaciano Graziela Mayara Nascimento Almeida | Arlete José Mota RESUMO O presente trabalho apresenta os resultados iniciais do projeto de pesquisa "Ritos e mitos na literatura augustana" e objetiva analisar o Carmen saeculare de Horácio, buscando enfatizar sua estruturação, os valores morais e políticos presentes no texto e a presença dos elementos ritualísticos relativos aos Jogos Seculares. Em termos metodológicos, optou-se por, após a tradução e pesquisas sobre a estruturação do poema, com base em Souza (2013), encetar um estudo a respeito dos ideais morais e políticos do homem romano observados no Carmen, tendo como ponto de partida as considerações de Maria Helena da Rocha Pereira (1990), e investigar a presença dos deuses e do herói Eneias, seguindo inicialmente a obra de Junito Brandão (1993) no que tange às versões dos mitos, além da escolha de Cassirer (2009) para as reflexões iniciais sobre o assunto.…”
unclassified